2002
DOI: 10.1080/00480169.2002.36255
|View full text |Cite
|
Sign up to set email alerts
|

Cilia-associated respiratory bacillus infection in rats in New Zealand

Abstract: CAR bacillus infection should be considered as a differential diagnosis for pneumonia in rats in New Zealand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…Conversely, microscopic lesions were very common, affecting substantial proportions of the study population. The results are in broad agreement with Brogden et al, 4 who found that 20 of 28 (71%) wild Norway rats had histological evidence of chronic respiratory disease, and with Laurain, 28 who briefly described pulmonary abscesses, but they differ from Kakrada et al, 24 who found only 2 of 27 wild rats affected by lung lesions. The inflammatory lesions observed in our study are similar to those described in pet rats and in early literature regarding laboratory rat pathology when laboratory animal pathogens were poorly controlled.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Conversely, microscopic lesions were very common, affecting substantial proportions of the study population. The results are in broad agreement with Brogden et al, 4 who found that 20 of 28 (71%) wild Norway rats had histological evidence of chronic respiratory disease, and with Laurain, 28 who briefly described pulmonary abscesses, but they differ from Kakrada et al, 24 who found only 2 of 27 wild rats affected by lung lesions. The inflammatory lesions observed in our study are similar to those described in pet rats and in early literature regarding laboratory rat pathology when laboratory animal pathogens were poorly controlled.…”
Section: Discussionsupporting
confidence: 89%
“…2 It has been identified at high apparent prevalence (52%-86%) in wild rats from Maryland, Texas, Iowa, and New Zealand. 4,11,24,31 The lower prevalence in this study (37%) may reflect our use of light microscopy for screening rather than more sensitive PCR tests. There was significant agreement between PCR and light microscopy results, and thus, light microscopy remains a useful and inexpensive method for detection of this bacterium.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Experimental infections have been established in rats [17][18][19], goats [20], mice, rabbits [21,22], guinea pigs [21], hamsters [22] and gerbils [23]. Filobacterium rodentium causes bronchopneumonia in wild rats in various parts of the world [2,24,25] and it contributes to the morbidity and mortality associated with polymicrobial respiratory infections in wild and laboratory rodents [26].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of disease in wild rats have been limited by small sample sizes and/or a narrow focus on specific pathogens or disease processes. 10,28,38,41,54,64,67,90,99 Studies by our group describe respiratory and cardiovascular pathology, as well as lesions associated with Capillaria hepatica, Eucoleus sp., and Notoedres muris infections. 1,[83][84][85][86] Many historical studies of wild rat disease describe obvious and common gross anatomic lesions (e.g., chronic lung disease and C. hepatica infection of the liver) rather than undertaking a systematic histologic evaluation of major organ systems.…”
Section: Introductionmentioning
confidence: 99%